Sobre AntropologED;a Cibernetica De La Arquitectura (Global Journal of Human-Social Science, 2022)
The present work aims to propose the necessary bases for an anthropology of architecture from the cybernetic approach that is the science that studies the processes of communication and control present in technical biological and social devices For this purpose the cybernetic notion of self- organization is used at its different levels of complexity according to the movement of reality to be addressed in its relations with architecture that is physical biological and social reality self-organization self-eco- organization and self-eco-production
Keywords: cybernetic anthropology; communication and control; complexity; self-organiza tion; self-eco-organization; self-eco-production